Role of AI in Reducing Honking in Electric Cars in India - Arindam Bindlish; Dr. Meghna Sharma (International Journal of Scientific Research in Science, Engineering and Technology, 2024)
This research paper studies the challenges of excessive honking in India and the possible opportunities of role of Artificial Intelligence in mitigating these issues. This paper explores the causes and impacts of honking to the citizens of the country and analysis the challenges faced by the car manufactures on how honking issue can be eradicated though AI. AI can contribute by analyzing the data which can help to understand the causes and solutions through implementation of the right algorithms for human behavior, road safety enhancement and improving the driving experience. This paper proposes valuable insights to Electric car vehicle manufacturers on how Artificial Intelligence can play a vital role in reducing the car honking in India.
Keywords: Noise Pollution; Car Honking; Driving Experience; Insurance Policies; Electric Car Models